ANGGARAN DAN PENGUKURAN KINERJA SEKOLAH (SMU) - Muhroji Muhroji (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2012)
This article presents high school budgeting and the significance high school performance measurement and why the relation between high school budget and high school performance measurement. A budget is a document that proposes income and expenditures for an annual period. The annual budget becomes the dominant management tool for planning, organizing, coordinating and controlling activities. High school budgets may be used for co-ordinating the multipurpose activities of a high school. Performance measurement is a vital part of the new managerialism in high school. They essentially measures the productivity and efficiency. The results may be used for assessing the overal effectiveness and efficiency of the high school activities. High school budget is one of performance indicator. Measuring the performance of high school is difficult and calls for a complex mosaic of indicators. Performance indicators of a high school can be classified into: curriculum, student, teacher and officer, teaching aids and infra structure, school organization and management, financial and social participation